Photophoretic Levitation of Macroscopic Nanocardboard Plates. Issue 16 (20th February 2020) - Cortes, John; Stanczak, Christopher; Azadi, Mohsen; Narula, Maanav; Nicaise, Samuel M.; Hu, Howard; Bargatin, Igor
Abstract: Scaling down miniature rotorcraft and flapping‐wing flyers to sub‐centimeter dimensions is challenging due to complex electronics requirements, manufacturing limitations, and the increase in viscous damping at low Reynolds numbers. Photophoresis, or light‐driven fluid flow, was previously used to levitate solid particles without any moving parts, but only with sizes of 1–20 µm. Here, architected metamaterial plates with 50 nm thickness are leveraged to realize photophoretic levitation at the millimeter to centimeter scales. Instead of creating lift through conventional rotors or wings, the nanocardboard plates levitate due to light‐induced thermal transpiration through microchannels within the plates, enabled by their extremely low mass and thermal conductivity. At atmospheric pressure, the plates hover above a solid substrate at heights of ≈0.5 mm by creating an air cushion beneath the plate. Moreover, at reduced pressures (10–200 Pa), the increased speed of thermal transpiration through the plate's channels creates an air jet that enables mid‐air levitation and allows the plates to carry small payloads heavier than the plates themselves. The macroscopic metamaterial structures demonstrate the potential of this new mechanism of flight to realize nanotechnology‐enabled flying vehicles without any moving parts in the Earth's upper atmosphere and at the surface of other planets. Abstract : Solid particles can levitate using photophoresis—light‐driven airflow—but only when micrometer‐scale in size. However, hollow plates with nanoscale thickness and microscopic channels exhibit photophoretic levitation at millimeter and centimeter scales. Light‐driven thermal transpiration of air through the plate's channels creates jets that result in small‐height hovering at atmospheric pressure or mid‐air flight at reduced pressures, even allowing small payloads.